Agatha Christie : an autobiography - Christie, Agatha (London Harper Collins, 2008)
Agatha Christie's most absorbing mystery- the story of her own unusual life. She has put it all on record; her early romances; a broken(and a happy) marriage; strange events on the path to roaring success.
Keywords: Christie, Agatha, 1890-1976; Authors, English; Autobiography